Cell-mediated cytotoxicity for cultured autologous rheumatoid synovial membrane cells. - Neill, W A (1980)
Cytotoxicity tests were performed on cultured rheumatoid synovial membrane cells with autologous lymphocytes as effector cells. Three of 26 cultures were positive when tested at primary or first passage level, but on subsequent tests became negative. Tests based on an isotope-labelling technique and a micro-cytotoxicity assay were compared; the results appeared to correlate well. The expression of neoantigens on synovial cells was not demonstrated. Cultures initiated in medium containing hydrocortisone did not give rise to a population of synovial cells susceptible to immune lysis by autologous lymphocytes.